Sport within Muslim organizations in Norway: ethnic segregated activities as arena for integration. Issue 1 (2nd January 2016) - Walseth, Kristin
Abstract : During recent years, there has been a growing focus within sports research on ethnic minorities and their involvement in sports. In UK, studies show that Muslim organisations offering sports activities to their members are a common phenomenon. The establishment of sports clubs by minority groups has been met with scepticism from governmental bodies because it is perceived as a 'segregated' activity that does not contribute to integration. However, in Norway, no research has been conducted on the output of these establishments, something this paper hopes to redress in part. The paper reports on a research project which aimed to examine the role of Muslim organisations in Norway in the development of social capital and integration through sport. The theoretical approach to the study of integration has Putnam's concept and understanding of social capital as point of departure. The study is based on interviews with representatives of seven Muslim organisations (mosques) in Oslo as well as participant observation at two arrangements. The sports activities offered by the mosques are first and foremost used by the mosques as a tool to recruit and gather Muslim youth. The study reveals the integration aspect of the work conducted by the Muslim organisations. It is argued that the Muslim organisations' idea of supporting youth to become 'Norwegian Muslim' is built on an 'anti-racism multiculturalism' discourse which rejects assimilation. A key aspect of this discourse is that minorities turn a negative difference ascribed by the majority into a positive identity to be proud of. As such, the work emphasises the possibility of being both Muslim and well-integrated into Norwegian society. Hence, the article argues for an integration perspective that recognises the integration work being carried out by minority organisations, even though this work, in terms of social networks, has more of a bonding character.